KAJIAN ARTIKEL: POTENSI PLASMA NON TERMAL SEBAGAI KANDIDAT TERAPI MASTITIS SUBKLINIS - Elfahra Casanza Amalda; Farah Alhamidah; Yudit Oktanella; Muhammad Khuzain (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
Subclinical mastitis is the occurrence of inflammation in the parenchymal tissue of mammaryglands due to bacterial contamination that does not show clinical symptoms lead to impacted oneconomic losses. The highest incidence of subclinical mastitis is the presence of Staphylococcusaureus bacteria contamination. Subclinical mastitis in Indonesia is reported to reduce milk productionby up to 53.5%. Pathogenesis of Staphylococcus aureus occurs in the presence of biofilm formation asbacterial immune system to protecting itself from disinfectants and antibiotics. In the last few decades,the development of plasma technology has been widely used in the medical field as cancer therapy,reducing pain, accelerating wound healing and tissue sterilization. There is no study that using theconcept of utilizing Non Termal Plasma in the field of veterinary science, especially in mastitistherapy. Non Termal Plasma is able to decontaminate Staphylococcus aureus through inhibition anddestruction of biofilms. The mechanism of action of Non Termal Plasma in repairing mammary glandtissue is through the destruction of DNA in the Reactive Oxygen Species (ROS) process by increasingthe growth factor TGF-1 which accelerates the process normal cell regeneration. The objective ofthis study is to reviewing the efficacy of plasma non termal as subclinical mastitis theraphy. This studywas conducted through a narrative review approach by collecting international and nationalliterature with interval time of publication within 2010 – 2020.